Populist Securitization of Migration: the Anti-Immigrant Zafer Party Example in Türkiye - Ozoflu, Melek Aylin; Uyar, Merve Hazer Yigit; Altintop, Apak Kerem; Uyar, Can; Yiğit Uyar, Merve Hazer (Routledge Journals, Taylor & Francis Ltd, 2025)
Although T & uuml;rkiye is the largest refugee-hosting country in the world, the Zafer Party's (ZP) (English: Victory Party) discourse on migration as the pioneer representative of the European-style anti-immigrant right party example has been under-studied. To address this gap, this research examines the discursive practices of the ZP through the lens of populist securitization. It focuses on revealing how the ZP employs a people-centred appeal to securitization, explaining how the people are located within its populist discourse as a threatened object of reference and actor. In this way, it empirically contributes to the burgeoning literature bridging between populism and securitization theory. To this end, it conducts an extensive qualitative frame analysis of the party's manifesto, programme, press releases, public speeches uttered by party leader & Uuml;mit & Ouml;zda & gbreve;. The time frame of the research is designated as starting from the establishment of the ZP, i.e. 26 August 2021, to the Presidential and Parliamentary Elections in T & uuml;rkiye, i.e. 14 May 2023. The paper finds out that ZP combines populist and nationalist appeals by creating vertical (down/up) and horizontal (in/out) antagonisms, exhibiting parallels with similar tendencies in its European counterparts.
Ozoflu, Melek Aylin/0000-0002-9403-6957; Altintop, Apak Kerem/0000-0002-6854-1378; Uyar, Can/0000-0003-0135-8410
Keywords: International Migration; Populist Securitization; Populism And Security; T & Uuml; Rkiye; Zafer Party; Türkiye